Fish collagen is an important panallergen in the Japanese population. Issue 5 (8th February 2016) - Kobayashi, Y.; Akiyama, H.; Huge, J.; Kubota, H.; Chikazawa, S.; Satoh, T.; Miyake, T.; Uhara, H.; Okuyama, R.; Nakagawara, R.; Aihara, M.; Hamada‐Sato, N.
Abstract: Collagen was identified as a fish allergen in early 2000s. Although its allergenic potential has been suggested to be low, risks associated with collagen as a fish allergen have not been evaluated to a greater extent. In this study, we aimed to clarify the importance of collagen as a fish allergen. Our results showed that 50% of Japanese patients with fish allergy had immunoglobulin E (IgE) against mackerel collagen, whereas 44% had IgE against mackerel parvalbumin. IgE inhibition assay revealed high cross‐reactivity of mackerel collagen to 22 fish species (inhibition rates: 87–98%). Furthermore, a recently developed allergy test demonstrated that collagen triggered IgE cross‐linking on mast cells. These data indicate that fish collagen is an important and very common panallergen in fish consumed in Japan. The high rate of individuals' collagen allergy may be attributable to the traditional Japanese custom of raw fish consumption.